FACTORS ASSOCIATED WITH DIETARY COMPLIANCE WITH TYPE 2 DIABETES MELLITUS IN THE ELDERLY IN SOUTH TANGERANG - Murodi, Syifa Rezkya; Damiati, Nia; Yuanita, Ita; Setiowati, Dwi; Handayani, Maulina; Utomo, Waras Budi (Jurnal Keperawatan, 2025)
Diabetes mellitus is classified as one of the main causes of poor health in the world. One of the populations most at risk and increasing in number is the elderly. To achieve successful control of diabetes mellitus, one of them depends on dietary compliance. Dietary adherence is an important factor to keep blood sugar stable and not cause complications. This study aims to determine the factors associated with dietary compliance with type 2 diabetes mellitus in the elderly in the Pisangan Health Center area. This type of research is observational analytics with a cross sectional approach. The number of samples in this study was 70 respondents taken using purposive sampling techniques. The instruments in this study used demographic questionnaires, influencing factors, and PDAQ (Perceived Dietary Adherence Questionnaire). The results showed that there was a significant relationship between education, knowledge, and self-motivation with DM diet adherence. Meanwhile, there was no significant association between sex, occupation, family support, and the role of health workers with DM dietary adherence. In this study, there were 24 respondents with low diet adherence, and 46 respondents with high diet adherence. Researchers hope that health workers can pay more attention to groups that have not been exposed to information related to DM and DM diet management and can pay attention again to other factors that are less related to dietary compliance in the elderly.